(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2012)
It was studied the macroeconomic consequences of controlling energy related carbon dioxide emissions..Â The aims of this study is to modify a model by combining "top-down macroeconomic model" with "bottom-up model" to stabilize carbon dioxide emissions in the atmosphere with apply energy-efficiency technology to minimize carbon dioxide production. The parameters measured are carbon energy demand.Â The results showed that the energy-efficiency technology is a sufficient method to reduce carbon emissions, namely energy-related carbon dioxide emissions grew at 5.8% per year over 1976-1990 and, in future, it will from grow at 4.8% and 2.9% per year for the high and low base cases respectively.